Knowledge and perceptions about Dolutegravir and Dolutegravir counselling: a qualitative study among women living with HIV - John C. Chapola; Fan Lee; Agatha Bula; Nora E. Rosenberg; Jennifer Tseka; Maganizo Chagomerana; Mina C. Hosseinipour; Jennifer Hui-Yu Tang (BMC, 2023)
Abstract Introduction In 2018, the Malawi Ministry of Health adopted the recommendation to switch first-line antiretroviral therapy (ART) from an efavirenz (EFV)-based to a dolutegravir (DTG)-based regimen. Little is known about patients' experience during this transition. We conducted a qualitative study to explore DTG-related counselling challenges among providers of HIV care and factors influencing regimen switching or non-switching among women living with HIV in Lilongwe, Malawi. Methods Between February-July 2020, we recruited participants who took part in DTG counselling on reasons to switch, side effects, and benefits from two government health facilities providing HIV care: Area 18 health centre and Bwaila district hospital in Lilongwe, Malawi. We purposively sampled and interviewed 8 women living with HIV who remained on an EFV-based regimen after counselling, 10 women who switched to a DTG-based regimen, and 10 HIV care providers who provided counselling about ART switching. In-depth interviews were used to explore patient's perceptions of DTG, factors affecting the decision to switch, and both patient and provider experience with counselling. Interview data was coded for themes using inductive and deductive codes. Interviews were conducted until thematic saturation was achieved. Data matrices were used for analysis and thematic extraction. Results Most women in both groups were well versed on DTG's potential side effects and felt well counselled on the benefits of switching, such as quicker viral load suppression. Many women associated DTG with birth defects and expressed concern. However, the primary reason for not switching was concern with how the new medication would be tolerated, especially when they were satisfied with their current regimen. Almost all providers expressed difficulty providing DTG counselling. Primary reasons included feeling inadequately trained and/or not having resources to use during counselling, such as diagrams or brochures. Conclusion DTG counselling was well accepted by women; however, some felt that their concerns were not fully addressed. Providers reflected this sentiment in that they did not feel adequately trained or well-equipped to provide adequate counselling. Training on counselling for new ART regimens should be intensified and utilize patient-centered educational materials to address the concerns raised by both patients and health care providers.